Territory Availability at Different Spatial Scales does not Affect Fighting Investment in Males of the Lycaenid Butterfly Strymon mulucha. (22nd August 2016) - Ferreira, Cibele P. S.; Cerqueira, Luana P.; Uezu, Alexandre; Oliveira, Eddy J. F.; Peixoto, Paulo E. C.
Abstract: In territorial species, rivals investment in fights over territories may increase when the availability of suitable areas for defense is low. This should occur because low territory availability may increase the costs to maintain and acquire territories. Although such process occurs in small spatial scales (local scale), territory availability in larger scales (regional scale) may also affect fighting investment, as losers should incur additional dispersing costs to find new territories. In this study, we used males of the hilltopping butterfly Strymon mulucha to evaluate the hypothesis that males should invest more in territorial fights when the costs to find new territories are higher (both at local and at regional scale). We timed male–male contests for territories located in 12 hilltops and measured male density per territory in each hilltop (local scale). We also quantified the distance between hilltops containing suitable areas for territories (regional scale). Male–male contests lasted 21 s on average, and copulations did not occur during the observations. The duration of contests was unrelated to the male density per territory or to the distance among hilltops, indicating that the investment in fights was unaffected by the availability of territorial sites, independent of the spatial scale. As male–male contests in S. mulucha are longer than the mean contest duration in other butterfly species and mating is extremely rare, we suggest that the value of each territory may be high enough to favor males that always invest as much as possible in contests.